QTL mapping: insights into genomic regions governing component traits of yield under combined heat and drought stress in wheat - Manjunath, Karthik Kumar; Krishna, Hari; Devate, Narayana Bhat; Sunilkumar, V. P.; Patil, Sahana Police; Chauhan, Divya; Singh, Shweta; Kumar, Sudhir; Jain, Neelu; Singh, Gyanendra Pratap; Singh, Pradeep Kumar (Frontiers in Genetics, 2024)
Drought and heat frequently co-occur during crop growth leading to devastating yield loss. The knowledge of the genetic loci governing component traits of yield under combined drought and heat stress is essential for enhancing the climate resilience. The present study employed a mapping population of 180 Recombinant Inbred Lines (RILs) derived from a cross between GW322 and KAUZ to identify Quantitative Trait Loci (QTLs) governing the component traits of yield under heat and combined stress conditions. Phenotypic evaluation was conducted across two consecutive crop seasons (2021-22 and 2022-23) under late sown irrigation (LSIR) and late sown restricted irrigation (LSRI) conditions at ICAR-IARI, New Delhi. Various physiological and agronomic traits of importance were measured. Genotyping was carried out with 35K SNP Axiom Breeders genotyping array. The linkage map spanned a length of 6769.45 cM, ranging from 2.28 cM/marker in 1A to 14.21 cM/marker in 5D. A total of 35 QTLs were identified across 14 chromosomes with 6B containing the highest (7) number of QTLs. Out of 35 QTLs, 16 were major QTLs explaining the phenotypic variance greater than 10 percent. The study identified eight stable QTLs along with two hotspots on chromosome 6B and 5B. Five QTLs associated with traits TGW, NDVI and PH were successfully validated. Candidate genes encoding antioxidant enzymes, transcription factors and growth-related proteins were identified in the QTL regions. In silico expression analysis highlighted higher expression of transcripts TraesCS2D02G021000.1, TraesCS2D02G031000, TraesCS6A02G247900 and TraesCS6B02G421700 under stress conditions. These findings contribute to a deeper understanding of the genetic architecture underlying combined heat and drought tolerance in wheat, providing valuable insights for wheat improvement strategies under changing climatic conditions.